Project Based Learning Dan Loose Parts : Solusi Untuk Meningkatkan Kemampuan Kognitif Anak Usia Dini - Yuni Herlina; Rambat Nur Sasongko; Nina Kurniah; Betti Nuraini (PAUDIA: Jurnal Penelitian dalam Bidang Pendidikan Anak Usia Dini, 2026)
Learning in early childhood education remains largely teacher-centered and relies on limited learning media. This article presents the development of a loose parts–based Project-Based Learning (PjBL) model with the potential to enhance young children’s cognitive abilities and creativity. The model was developed in response to findings that early childhood education in Bengkulu City still emphasizes reading, writing, and arithmetic, with limited use of varied and open-ended learning materials. The study aimed to produce a loose parts–based PjBL model that is valid, practical, and feasible for early childhood learning. A Research and Development (R&D) approach was employed using the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. A limited trial involved 40 children, while a large-scale trial included 73 children from several PAUD units in Bengkulu City. Data were collected through observation, interviews, documentation, and performance assessments, and analyzed using a t-test. The results indicate that the final model consists of five learning phases and its implementation shows a tendency to improve children’s cognitive and creativity and is considered highly feasible and practical by teachers. This study contributes an applicable project-based learning model to support more child-centered early childhood education practices.